The White Planet : The Evolution and Future of Our Frozen World - Jouzel, Jean, 1947- (Book collections on Project MUSE., 2013)
From the Arctic Ocean and ice sheets of Greenland, to the glaciers of the Andes and Himalayas, to the great frozen desert of Antarctica, The White Planet takes readers on a spellbinding scientific journey through the shrinking world of ice and snow to tell the story of the expeditions and discoveries that have transformed our understanding of global climate. Written by three internationally renowned scientists at the center of many breakthroughs in ice core and climate science, this book provides an unparalleled firsthand account of how the ""white planet"" affects global climate--an.